THE AUTHORSHIP OF SHAYKH NAWAWI AL-BANTANI IN ARABIC LINGUISTICS STUDIES (State Islamic University (UIN) of Sunan Ampel Surabaya, 2023)
This paper delves into the distinctive significance and characteristics of Nawawi's linguistic thought within the Malay Muslim sphere, exploring their correlation with his broader Islamic paradigm. Utilizing the theoretical framework of knowledge production and authorship, the study reveals Nawawi's noteworthy contribution to Arabic linguistics in Indonesia. His comprehensive grasp of Islamic sciences infuses a unique discourse into the field, blending Arabic grammar intricacies with ethical and theological dimensions. Despite his profound expertise, Nawawi's impact on Indonesian Muslim society remains inadequately acknowledged. This oversight can be attributed to the prevailing curriculum in Indonesian pesantren, the influential presence of Arab-origin scholars, and restricted access to Nawawi's works. Unveiling this scholarly gap underscores the need for greater recognition of Nawawi's linguistic insights and their integration into the educational fabric of Islamic studies in Indonesia.